Social and cultural prerequisites for the development of managerial freedom in Russia and Europe: Comparative analysis - O A Zaytseva (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2015)
The sphere of management activities in contemporary organizations is undergoing through serious transformations; in particular, robotic production is becoming more common. In this situation, the importance of studying managers’ work at all organizational levels grows, especially at the middle level for its managers form the core of organization as having deep knowledge and experience, as well as regulating all daily operations. Managerial freedom in the work of middle level managers is a new response to the demands for innovative activities and competitiveness every organization faces. At the same time, globalization leads to the partnership between Russian and European companies, however, effectiveness of such relations depends largely on understanding social and cultural foundations of management. The article considers social and cultural prerequisites of managerial freedom in Russia and Europe focusing on the differences of Russian and European history of entrepreneurship, its backgrounds, key actors and functions of managers in former times. The author shows specific features of social institutions that formed the basis for the development of the business world and determined the very essence of managerial freedom.